2011
DOI: 10.3386/w17354
|View full text |Cite
|
Sign up to set email alerts
|

Leverage Across Firms, Banks, and Countries

Abstract: We present new stylized facts on bank and firm leverage for 2000-2009 using extensive internationally comparable micro level data from several countries. The main result is that there was very little buildup in leverage for the average non-financial firm and commercial bank before the crisis, but the picture was quite different for large commercial banks in the United States and for investment banks worldwide. We document the following patterns: a) there was an increase in leverage ratios of investment banks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…Yet, MFIs' leverage ratios remain much lower than those of traditional banks. For instance, Kalemli-Ozcan et al (2012) analyzed 180,460 banks and found a mean equity of USD 0.8 billion and a mean debt of USD 10.7 billion, which makes a debt-to-equity ratio of 13.37.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Yet, MFIs' leverage ratios remain much lower than those of traditional banks. For instance, Kalemli-Ozcan et al (2012) analyzed 180,460 banks and found a mean equity of USD 0.8 billion and a mean debt of USD 10.7 billion, which makes a debt-to-equity ratio of 13.37.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Investment bank presence both in terms of number of institutions and operations is centred in these countries (Kalemli-Ozcan, 2012;Thomson Reuters, 2012). The development of investment banking activities reached its peak in 2006, when the industry's total income in the G7 and Switzerland amounted to 80.67 (US$bn).…”
Section: Introductionmentioning
confidence: 99%
“…17 The relationship between efficiency, bank size and leverage in the model is consistent with the data as shown in section 5.3. See also Kalemli-Ozcan et al (2012) who find that larger banks have a higher leverage.…”
mentioning
confidence: 99%